Death of a Discipline Twentieth Anniversary Edition. - Spivak, Gayatri Chakravorty (The Wellek Library Lectures., 2023)
Gayatri Chakravorty Spivak declares the death of comparative literature as we know it and sounds an urgent call for a "new comparative literature," in which the discipline is reborn.